1962
DOI: 10.1017/s0373463300020312
|View full text |Cite
|
Sign up to set email alerts
|

II—R. C. Alabaster

Abstract: At present the rate of failure of a weather radar set is of the order of 1 failure in 50 sector flights. Probably the most reliable unit of the equipment is the scanner, which is fortunate because it is the most difficult unit to locate in an aircraft by virtue of its size and the need for uninterrupted forward scanning. With its present size the installation of two scanners is not feasible. In a piston-engined aircraft a radar failure when confronted by prolonged turbulent cloud conditions means no loss of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Pimobendan is reported to elevate cmp and has all the characteristics of a P D E inhibitor but in addition prolongs the action potential duration which may be an additional mechanism of its inotropic me bradycardia produced by the quinazolines, buquineran and carbazeran, is an unusual (though attractive) feature of P D E inhibitors. Alabaster et al (1977) demonstrated that buquineran increased guineapig atrial force and reduced rate, thereby resembling their findings with ouabain. Buquineran was found to inhibit the P D E enzyme but since it did not affect Na+,K+-ATPase activity, then the mechanism of the bradycardia remains a mystery.…”
Section: Discussionmentioning
confidence: 62%
“…Pimobendan is reported to elevate cmp and has all the characteristics of a P D E inhibitor but in addition prolongs the action potential duration which may be an additional mechanism of its inotropic me bradycardia produced by the quinazolines, buquineran and carbazeran, is an unusual (though attractive) feature of P D E inhibitors. Alabaster et al (1977) demonstrated that buquineran increased guineapig atrial force and reduced rate, thereby resembling their findings with ouabain. Buquineran was found to inhibit the P D E enzyme but since it did not affect Na+,K+-ATPase activity, then the mechanism of the bradycardia remains a mystery.…”
Section: Discussionmentioning
confidence: 62%
“…Paralaurionite, a dimorph of laurionite, has not been observed in any titration. This is of significance as the two minerals occur in association with one another in certain deposits, including the Wesley Mine, near Bristol (Alabaster, 1989) and in the Laurium slags (Palache, 1934). It is not absolutely certain whether laurionite is the thermodynamically stable phase at ambient temperatures; paralaurionite is known, for example, in comparatively large amounts in the Mammoth-St. Anthony Mine, Tiger, Arizona (Bideaux, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…3 This illustrates the interrelationships between the various lead hydroxychloride phases. Under natural saline conditions, seawater for example, where approximate chloride concentrations are 0.5 M, and the pH is about 8, the preferred phase to crystallise would be laurionite or its dimorph paralaurionite (no distinction is made here between the two), and this is reflected by frequency of reports of its occurrence under such conditions (Russell, 1920;Palache, 1934;Palache etal., 1951;Kohlberger, 1976;Campbell and Mills, 1977;Symes and Embrey, 1977;Bideaux, 1980;Schnorrer-KOhler, 1986;Schnorrer-KOhler etal., 1988;Alabaster, 1989). Reduction of salinity or an increase of pH gives rise to conditions when blixite can form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example the prejunctional C2-adrenoceptors in vas deferens of rat and rabbit had a different antagonist potency series, yohimbine being more potent than Wy26703 in the rabbit but less potent in the rat. It was subsequently found that the potency of each antagonist at postjunctional a2-adrenoceptors in the rabbit saphenous vein was similar to that found at the prejunctional M2-adrenoceptors in rabbit vas deferens (Alabaster et al, 1986).…”
Section: Introductionmentioning
confidence: 77%